THE ABILITY TO WRITE NEGOTIATED TEXT ON MULTIMEDIA GRADE X STUDENTS OF SMKN 10 MEDAN IN ACADEMIC YEAR 2019/2020 - Radani, Nur; Hutagalung, Trisnawati (Universitas Hamzanwadi, 2020)
This research aims to analyze the negotiating text writing skills of students of grade X Multimedia of SMKN 10 Medan Year of Learning 2019/2020. The method used in this study is a descriptive method. The population of this study is all students grade X Multimedia of SMKN 10 Medan Year of Learning 2019/2020 consisting of 3 classes with a total of 104 students. Sampling was done by random sampling technique and selected class X Multimedia 1 with a total of 34 students. The research instrument used is the essai test of writing the negotiating text with regard to the structure and linguistic rules of the text. The data collection techniques in this study are assignments. The data in this study is a score of negotiating text writing ability. The results showed that students negotiating text writing skills based on aspects of the structure were divided into an average score opener of 100, an average score of 97.24, and a closing score of 76.68 while the aspects of language rules were divided into news sentences, questions and The command average score is 78.49, the sentence the wish score is the average score 35.29 the conditional sentence the average score is 52.20 and the conjunction causes the average score is 55.88. So the results show that class X Multimedia at of SMKN 10 Medan in writing negotiating texts with the total average score of the two aspects is 69.70 in the sufficient category. Keywords: Ability, Writing, Text Negotiation.